Communication Strategies Towards Preventing Violent Extremist Attacks in Pakistan - Mustaqeem, Sundus; Dalib, Syarizan; Ramli, Romlah (South Asian Journal of Social Sciences and Humanities, 2020)
With unpredictable purposes, extremism in Pakistan has attracted considerable local and global attention, especially after 9/11. Due to war against terrorism, Pakistan has suffered tremendous losses both in terms of number of precious lives and billions of dollars in foreign investment; economic terrorism imposed by foreign sponsored and homegrown terrorist networks. The country has been facing the challenging situations in the form of target killings and bomb blasts. On 16 December 2014 the brutal terrorist attack on Army Public School (APS) in Peshawar Pakistan appeared as major catastrophe, as killing children has become a major puzzle to our understanding of terrorism. This research examines the consequences of extremist attacks in Pakistan while revealing APS attack and argues that communication strategies can be assimilated into policies as preventive measures to minimize extremism and establish peace. To investigate this, qualitative methodology has been used, based on in-depth interviews to provide comprehensive perspectives from field experts and practitioners, affiliated with the same area. Thus, with the observations of 13 Informants, the study revealed that strategic communication for countering violence extremism from both the long-term and short-time strategic approaches are expedient. The study discovered that plausible communication strategies required to counter violent extremist need to underscore preventive communication strategies and consistent use of credible sources of information. In order to support the findings, models were generated through NVivo 10. Finally, it is recommended that communication strategies should convey healthy messages regarding conduct and aptitude to far-reaching populations through media and other sources of communication.